Yield Stability and Resistance of Five Melon Genotypes (Cucumis melo L.) Cultivated On Three Altitude Areas - Muhammad Iqbal (Vegetalika, 2018)
The study was conducted to determine the yield stabilities of five melon varieties tested at three altitude areas and to obtain a variety of melon whose yield and stability exceed at three altitude areas. The study examined five melon varieties, namely 'Golden Aroma', 'Ladika', King Melon, Bravo, and M19 at three altitudes, namely Jombang (lowland 52 m dpl), Jiput (mediumland 460 m dpl), and Bojong (highland 776 m dpl) using a complete randomized block design (RAKL) with four replicates (blocks). The study was conducted during the rainy season in October 2016-January 2017 (in Jombang), November 2016-February 2017 (in Jiput), and March 2017-June 2017 (in Bojong). The results showed that the varieties that had yield per hectare and genotype resistance to the environment exceeded the general average were the varieties of King Melon and Bravo, although both of them were unstable at three altitude areas. Average yield per hectare for King Melon (19.33 ton/ha) and Bravo (18.21 ton/ha) and genotype resistance to the environment for King Melon (65.42%) and Bravo (56.25%) were superior to the commercial varieties of 'Golden Aroma' and 'Ladika' and able to compete with national melon yields in 2013 (17.71 ton/ha) and 2014 (18.37 ton/ha).